Efficiency of budesonide delivery via a mesh nebulizer in an in‐vitro neonatal ventilator model. Issue 9 (23rd June 2020) - Esmaeilizand, Rana; Rocha, Taciano; Harrison, Ava; Gray, Shari; Fusch, Gerhard; Dolovich, Myrna; Mukerji, Amit
Abstract: Objective: To determine the delivery efficiency of budesonide aerosol via a mesh nebulizer in a neonatal ventilator model. Design/Method: In an in‐vitro ventilated neonatal model, budesonide suspension was administered using a mesh nebulizer. A collection filter was placed distal to the endotracheal tube and budesonide captured by the filter was measured using UV spectroscopy. The ventilator was, in turn, either on high frequency or conventional ventilation mode and the nebulizer was placed either proximal (close to the endotracheal tube) or distal (between the wet side of humidifier and the inspiratory circuit). Each combination (nebulizer position and ventilation mode) to assess budesonide delivery was tested five times. Results: Overall delivery of budesonide to the distal end of the endotracheal tube a small percentage of the total dose administered. The deposition with conventional ventilation was 2.12% (±1.06) and 1.26% (±0.27), with proximal and distal placement of the nebulizer, respectively. With high‐frequency ventilation, the deposition percentages were 1.82% (±0.82) and 1.69% (±0.23), with proximal and distal nebulizer placement, respectively. Conclusion: Only a small percentage of administered budesonide is delivered to the distal endotracheal tube, irrespective of ventilation mode, and nebulizer placement.